Refractive lens exchange with a trifocal intraocular lens in Fuchs endothelial dystrophy. Issue 3 (March 2020) - Nanavaty, Mayank A.; Ashena, Zahra
Abstract : A 57-year-old man with myopia presented with advanced Fuchs endothelial dystrophy, a refraction of −6.00 diopters (D) and −6.25 D, an endothelial cell count of 1100 cells/mm 2 and 1000 cells/mm 2 in right and left eyes, respectively, and corrected distance visual acuity of 20/30 in each eye. The patient was deemed unsuitable for excimer or femtosecond laser–based refractive surgery or refractive lens exchange (RLE) with a trifocal intraocular lens (IOL) alone because of the advanced Fuchs endothelial dystrophy and high risk of corneal decompensation and reduced optical quality postoperatively. A successful RLE with a hydrophobic trifocal IOL and Descemet membrane endothelial keratoplasty in both eyes was performed at an interval of 2 months between the eyes. At 12 months, the uncorrected distance visual acuity was 20/16 in each eye, with uncorrected near visual acuity of 20/20 for 40 to 60 cm from the face. The endothelial cell count at 12 months was 2250 cells/mm 2 and 2120 cells/mm 2 in right and left eyes, respectively.